Mechanistic study on DNA-directed assembly of gold nanoparticles for biosensing applications. - Lee, Kwai Han. (2011)
Gold nanoparticles have been used for colorimetric sensing due to its unique optical properties arises from localized surface plasmon resonance (LSPR). Its interparticle distance-dependent LSPR is highly tunable by programmable DNA-directed AuNPs assembly. With this, a rapid protein sensing assay using the assembly of 2 sets of double-stranded DNA(dsDNA)-grafted AuNPs, crosslinked by short complimentary single bases has been initiated by Tan et al.The desired protein is detected when a massive aggregation which occurs immediately at elevated salt condition, is retarded by specific protein binding. Despite of the rapidity and specificity, protein stabilization approach eliminates the occurrence of false positives due to non-specific destabilizers. Hence, a mechanistic study on its DNA design is reported here to provide a deeper insight into the assay design. Controllability of assembly kinetics by DNA spacer rigidity relying on dsDNA and ssDNA composition is studied, in which a long rigid dsDNA spacer is found to be the most favourable for rapid assembly. An optimum length of the crosslinking single bases is required to provide an adequate base-pairing force while containing the ssDNA random coiling effect. Despite, compatibility of the assay design to competition format is proven, allowing direct addition of unmodified DNA analyte for protein sequence recognition testing, without the need of multiple AuNPs conjugations with each analyte sequence. This assay design offers an alternative for convenient yet specific and highly reliable biosensors development, which could be extend to a wide range of DNA-binding molecules sensing.